Teori Perkembangan Bahasa Anak dan Implikasinya terhadap Kurikulum Merdeka di Sekolah Dasar: Teori Perkembangan Bahasa Anak dan Implikasinya terhadap Kurikulum Merdeka di Sekolah Dasar - Muhammad Arya trymanda; Silvina Noviyanti; Jepri Alfiansyah; Muhammmad Rezki Alfian (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study examines the integration of child language development theories (Chomsky’s nativism, Skinner’s behaviorism, and Piaget-Vygotsky’s constructivism) into the implementation of the Kurikulum Merdeka (Independent Curriculum) in elementary schools using a library research approach with content analysis. The findings reveal that these three theories are complementary and highly relevant to the principles of Kurikulum Merdeka, which emphasize active, contextual, collaborative, and student-potential-based learning. The integrated application of these theories through strategies such as project-based learning, role-playing, storytelling, discussion, and scaffolding has been proven to significantly enhance children’s speaking, listening, reading, and writing skills while supporting the development of literacy and critical thinking. Nevertheless, the main challenges lie in teachers’ readiness to understand and effectively implement the theories, the need for continuous training, and the provision of supportive learning environments and resources. This study recommends strengthening teacher competence through training based on language development theories and developing holistic and adaptive language teaching models so that Kurikulum Merdeka can be optimally utilized to sustainably support language development in elementary school-aged children.